EKSTRAK DAUN SIRSAK (Annona muricata L.) SEBAGAI ANTIOKSIDAN PADA PENURUNAN KADAR ASAM URAT TIKUS WISTAR - Ni Putu Rahayu Artini; Sri Wahjuni; Wahyu Dwijani Sulihingtyas (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of anti-oxidant  active isolate from soursop leave (Annona muricata L.) was carried out in this study. Methanol was used to macerate an 158 gram sample. This crude extract showed 77,22% of inhibition ability to reduce oxidation of DPPH (difenil-picrylhydrazine) at the fifth minute and 85,42% at the sixtieth minute inhibition time. Petroleum benzene, chloroform, n-buthanol, and water were applied to separate it. N-buthanol extract has the highest anti-oxidant reduction percentage which was 91,10% of inhibition ability to reduce oxidation at the fifth minute and 97,90% at the sixtieth minute inhibition time. From this research, it was obtained that the best dose of n-buthanol fraction applied to decrease uric acid was 200 mg/Kg BW with a percentage decrease of 86,29% (p=0,001).n-buthanol  fraction was identified by gas chromatography-mass spectrometer. The active compounds observed were: benzofuran,2,3-dihidro; tetradecana;  3-ethoxy-1,4,4a,5,6,7,8,8a-octahydroisoquinoline;  2-cyclohexen-1-one, 4-hydroxy-3,5,6-trimethyl-4-(3-oxo-1-butenyl). In conclusion, soursop leave (Annona muricata L.) extract  was active for decreasing uric acid of rat tested. For future research, this method could be applied to human in decreasing uric acid concentration in blood.